The development of an effective energy management framework for energy efficient buildings - Mohamad Zamhari, Tahir (2019)
Energy management in government office buildings is to ensure continuous energy efficiency over a long period of time by applying the methods that suit the needs and the budget. Effective energy management is not only to achieve and maintain optimum energy consumption and to minimize energy costs, but also to ensure that its performance will not affect the performance and quality as well as to maintain the energy efficiency levels that has been achieved. The achievement of energy efficiency is continuous through the involvement of various parties concerned. Therefore, effective energy management programs could improve energy efficiency in the government office buildings with several criteria and practices, establishing good cooperation between top management, employees, energy management committee and various teams. This research aims to develop a framework for improving the energy efficiency practices for a more effective energy management environment. The thesis begins with a review of the literature on energy management concepts, issues, advantages and the importance of increasing the consideration of energy efficiency measures in the office building. Existing references and interviews show how common practices do not involve the relationship between top management, employees and energy management committees in ensuring the implementation of energy efficiency practices more effective and sustainable. A framework of working practices for improving the energy management program is based from three case studies as well as analysis of literatures and insights from the experts. The results from analysis of the case studies show that energy efficiency programs and activities can be implemented well through the involvement and cooperation of many parties with the guidance on energy management planning, implementation, monitoring and evaluation that help them to improve building performance. Therefore, the framework developed within the research, provides team leaders or energy managers with a holistic and structured approach for achieving energy efficient buildings through the appropriate practices of the effective energy management program. Recommendation for future work may focus studies on a larger scale to investigate other government-owned buildings and taking into account as well the technical aspects of technology so that the approach of the study becomes more comprehensive, integrated and systematic.